Improving the Students Reading Comprehension by Using Scaffolded Reading Experiences (SRE) Strategy - Ndraha, Warni Lesta Putri; Waruwu, Yaredi; Daeli, Hidayati; Harefa, Afore Tahir (Edumaspul: Jurnal Pendidikan, 2023)
Reading is one of the important basic skill in learning English besides Listening, Speaking and Writing. Reading activity has one of the ways to catch up information, to know enough science concepts, to know more knowledge, to understand scientifics books , Through reading in reader may have satisfication and comfort. The were some problems namely : The students are not able  to identify the generic structure of text, The students can not identify the main idea of  text, The students not able to find social function of text, The students had difficulty to find characteristics of text. The students have difficulty to find the language features of text. To overcome the problems, the researcher was implemented Scaffolded Reading Experience (SRE) Strategy. The purpose of the research was to improving the students reading comprehension narrative text by using Scaffolded Reading Experience (SRE) Strategy at the tenth grade of SMA Swasta Kristen BNKP Gunungsitoli in 2022/2023. The research method was Classroom Action Research (CAR) especially Quantitative method. The subject of research was the tenth grade  of SMA Swasta Kristen BNKP Gunungsitoli which the total number of the students was 24 students. The researcher has conducted in two cycles. Each cycles consists of two meeting. In collecting the data, the researcher used observation sheet, field notes and evaluation sheet. The result of the data in Cycle I that there  were 2 students (8%) in fail level, 10 students ( 42%) less level, 6 students (25%) in the enough level, 6 students (25%) in the good level and 0 students in the very good level. The average of the students’ value was 63.58%. This result showed that the students were unsuccessful. In Cycle II that there were 16 students (33.34%) in the Good Level and 8 students (66.66%) in the very good level. The average of the students’ value is 82.50%. Finally, the researcher gave some suggestions as follows: (1) the researcher suggested to the students to be confidence to convey their text to share experience idea if the teacher implement Scaffolded Reading Experience ( SRE) Strategy in teaching comprehension. (2) the teacher was to give a reminder to the students that in giving the response they should do it by themselves without depending on the other friends. (3) the researcher suggested all readers especially to the next researchers to explore how to easy to find main idea of the text that had not been explored by the researcher in the research.